RETRACTED: Mathematical modeling of heliothermal chemical processes during hardening of multicomponent cement materials - Alinazarov A.Kh.; Salimzhanov Zh.Kh. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001